UTILIZATION OF VIDEO MEDIA IN NEGOTIATION TEXT LEARNING IN CLASS X MAN 2 SOLOK - Susanti Marisya; Zuraida Chairani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
This research is motivated by the lack of interest of students in participating in the negotiation text learning process. Students do not focus on listening to the learning material delivered so that students find it difficult to write negotiating texts. The students' writing tends not to match the criteria in writing the correct negotiating text so that the student's score is low. Most of the conventional methods are still used by teachers in delivering negotiation text material. Teachers should be able to develop strategies and methods that are creative, interesting so that students become enthusiastic and enthusiastic in learning. One of them is by using learning video media. The purpose of this study is to describe the use of video media in learning negotiation texts. This type of research is descriptive quantitative research. The population in the study were all students of class X, amounting to 86 students. The sample used is total sampling, namely all students of class X totaling 86. The instrument used is a questionnaire, with research data from the distribution of questionnaires using negotiation text learning media. Data analysis technique using descriptive statistical analysis. The results showed that the use of video media in negotiating text learning obtained an average score of 3.25 with an achievement level of 64.57%. Which is in the high category. This means that video media can be used as an alternative in delivering negotiation text learning materials.